Depuration of microcystin-LR from the red swamp crayfish Procambarus clarkii with assessment of its food quality - Tricarico, Elena; Bertocchi, Silvia; Brusconi, Sara; Casalone, Enrico; Gherardi, Francesca; Giorgi, Gianluca; Mastromei, Giorgio; Parisi, Giuliana (Aquaculture, 2008)
In the latest years, blooms of toxic Cyanobacteria have intensified worldwide, causing serious problems to human health. The edible crayfish Procambarus clarkii is known to accumulate the toxins (microcystins) produced by Microcystis aeruginosa. Our aims here were to (1) quantify microcystin-LR in P. clarkii's organs/tissues; (2) analyse differences in its content between size classes and between sexes; (3) develop protocols for the depuration of the toxin from crayfish; and (4) assess the quality of the crayfish abdominal muscle during depuration. The study was composed of two phases. In the first, the concentration of microcystin-LR in the hepatopancreas, stomach, intestine, and abdominal muscle of 102 crayfish was measured by the means of ELISA and was compared between small and large individuals and between sexes. In the second phase, 136 crayfish (64 males and 64 females) were subject to depuration for a maximum period of 21 days under two feeding regimes ( ad libitum, i.e. fed every day or restricted, i.e. once every third day). Sixteen crayfish were sacrificed at different times from the start of the treatment (3, 6, 9, 14, 17, and 21 days). Microcystin-LR was measured in the intestines and in the abdominal muscles of the treated crayfish and was compared to the values obtained from individuals sacrificed immediately upon capture. The abdominal muscle was also analysed for its quality by quantifying colour, water holding capacity, and composition (qualitative and quantitative) of the total lipids and fatty acids. The results showed that (1) P. clarkii accumulates more toxin in the intestine and less in the abdominal muscle (the edible part); (2) microcystin-LR is less abundant in large (the marketable size) than in small individuals; and (3) its content differs between sexes in the hepatopancreas only. Besides, (4) microcystin-LR content decreased in the abdominal muscle, but not in the intestine, after a short period of depuration in the two feeding regimes and (5) depuration did not reduce the overall quality of crayfish meat.